If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -10x = 39 + -31x Solving 9 + -10x = 39 + -31x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '31x' to each side of the equation. 9 + -10x + 31x = 39 + -31x + 31x Combine like terms: -10x + 31x = 21x 9 + 21x = 39 + -31x + 31x Combine like terms: -31x + 31x = 0 9 + 21x = 39 + 0 9 + 21x = 39 Add '-9' to each side of the equation. 9 + -9 + 21x = 39 + -9 Combine like terms: 9 + -9 = 0 0 + 21x = 39 + -9 21x = 39 + -9 Combine like terms: 39 + -9 = 30 21x = 30 Divide each side by '21'. x = 1.428571429 Simplifying x = 1.428571429
| Y^2+13Y-64=0 | | 109-3x=15x+21 | | [14-8(x-5y)+10(3x+y)]= | | 12+14r+9m-2r-3m+25= | | 4y-x-35=0 | | [14-8(x-5y)+10(3x-y)]= | | 10z-13z= | | 3=-4-Z | | 10(8x+9)=50 | | 4c^2-25d^2=0 | | 2[2(x+y)-3(6x-6y)]= | | X+5=145 | | 2x-5=6x+3 | | 6x+4(9x+5)= | | 6(7+10x)=-78 | | -16t^2+16t+32= | | 9y^2-162y+585=0 | | 3x[6x^2-4(x-1)]= | | -0.428p=-2 | | -4-6= | | (x+8)*(x+8)=44 | | 3(y-.8)+2y=.5 | | 12x^2+10x=8 | | 18z=-8 | | 19x=-6 | | 0y-x-3=0 | | 27+10=4x-5x | | 4y-x-10=0 | | -21=n+12 | | 6(c-3d)-(4c+d)= | | 6(c-3d)-(4c+d)=0 | | -21=9+12 |